Art Education in Latgale in the 20th-21st Century - Paurs, Vladislavs (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
In his paper the author deals with the origin of art education and the ways of its development in Latgale. The first significant art school was founded in Daugavpils in the 1920s and operated till the middle of the 20th century. After changing the statehood of Latvia during World War II it was reorganized into a vocational school and was closed in the post-war period. In the 1950s due to the initiative of Latgalian culture enthusiasts there was opened Rezekne Branch of Riga Secondary School of Applied Art. The school is still existing and functioning nowadays as a Secondary School Of Design and Art. In 1990 there was observed a significant change in art education when there was opened the first higher education institution of art in Rezekne – Latgale Branch of Art Academy of Latvia. Later on in 1992 in Daugavpils there was renewed “Sun School” and in 1996 at Daugavpils University there was founded the Art Department. In 2006 the first students of design programs were enrolled into the Faculty of Education and Design of Rezekne Higher Education Institution. Opening of art schools contributed to: - increase of cultural and educational level in Latgale; - development of skills in obtaining crafts of applied arts; - facilitation of the art's understanding in the society; - creation of opportunities to organize art education in Latgale. Existence of art schools encouraged: - to improve education of teachers and lecturers and develop creative skills; - to motivate students to participate in cultural activities and exhibitions; - to improve and develop the traditional types of Latgale applied art in a creative way. Art education in the 20th-21st Century gave opportunities: - to obtain higher education in art in Latgale, acquire new professions in the field of art and design; - to improve competences of teaching staff in exhibitions, workshops, conferences, projects; - to increase the creative-scientific level of lecturers by participation in international exhibitions and conferences; - to cooperate with universities in Latvia and abroad, exchange art exhibitions of their students and lecturers. In the 20th-21st Century there is a wide vocational network of art schools in Latgale. There are established two art secondary schools and three higher education institutions where artists or designers can acquire the appropriate education.